Pengembangan Media Pembelajaran Bahasa Inggris Flash Card Comic Kelas IV SDN 060872 Medan - Angeleva Revi Christa Sinaga; Dody Feliks Pandimun Ambarita; Lala Jelita Ananda; Albert Pauli Sirait; Tiarnita Maria Sarjani Br. Siregar; Charles Fransiscus Ambarita (Universitas Negeri Medan, 2025)
This research aims to determine the feasibility, practicality, and effectiveness of Flash Card Comic learning media for